E-Tools for Personalizing Learning During the Pandemic: Case Study of an Innovative Solution for Remote Teaching - Patrascoiu, Loredana Adriana; Folostina, Ruxandra; Patzelt, Dan; Blaj, Maria Paula; Poptean, Bianca (Frontiers in Psychology, 2022)
“Every child counts” has lost its value even from the political discourse of some societies during the pandemic, proving that the level of culture of inclusion is the true standard of Sustainable Development Goal (SDG) commitment. Online education and therapy required rethinking the way we educate children with special needs and, implicitly, prepare them for life. We consider that the personalized approach of the therapeutic intervention was the main difficulty. In this article, we propose a solution to this problem, an approach based on a platform initially developed by tactileimages.org for vision-impaired pupils which became a tool in the universal design of learning materials. This e-learning tool includes an Editor, a browser-based software developed to allow the creation or adaptation of drawings into vector images; the QR code through which areas of educational and therapeutic interest are allocated to pictures for task personalization; and the voice-over function of the companion application. The customized material is identified by image recognition algorithms, and the user's gesture is recognized by artificial intelligence algorithms, which receives (by voice-over) details about therapeutic tasks in remote teaching. The article illustrates the personalization of the therapeutic and educational path. The process starts with defining the child's functioning profile and matching function with the curriculum elements as they are found within the Erasmus + project “Cognitive Resources for Toddlers Teens and Experts” —stored in the virtual library. Information and comunication technology is currently an important vector in attaining the SDG vision. The proposed solution will be improved in order to further personalize the educational and therapeutic intervention in the post-pandemic period too.